Progesterone for preparation of the endometrium for frozen–thawed blastocyst transfer in vitro fertilization cycles: a prospective study on patients' opinions on a new subcutaneous formulation. (2nd September 2018) - Venturella, Roberta; Vaiarelli, Alberto; Buffo, Laura; D'alessandro, Pietro; Colamaria, Silvia; Pedri, Sara; Di Carlo, Costantino; Alviggi, Erminia; Forte, Marina; Faustini, Federica; Zullo, Fulvio; Rienzi, Laura; et al.
Abstract: We aimed to evaluate patients' perspectives on a progesterone subcutaneous formulation for endometrial preparation for frozen-thawed blastocyst transfer. In this prospective study, women with at least one experience with vaginal progesterone, undergone endometrial preparation with oral estradiol valerate and daily subcutaneous progesterone administered from the fifth day before the transfer until the day of the beta-hCG test. Patients completed three questionnaires, at enrollment (Q1), for gathering information on the experience with vaginal treatment and expectations about the subcutaneous route and then at the time of the transfer (Q2) and eight days later (Q3). Main outcome measures were patients' opinions on comfort, ease of use, convenience, overall satisfaction, level of anxiety and pain associated with the administration of subcutaneous progesterone in comparison with their previous experience. Sixty-nine women completed the questionnaires. All vaginal versus subcutaneous comparisons were significantly in favor of the subcutaneous route. When comparing patients' expectations at Q1 with patients' opinions at Q2 and Q3, all evaluations, except for one, demonstrated that the patient's positive expectation was confirmed after 5 and 13 days of treatment. In conclusion, in women with previous experience with vaginal progesterone, the subcutaneous route was associated with significantly increased acceptance.